Identification and Characterization of Fiber Optic Imaging Bundle Structures in Endoscopic Fringe Projection Systems - Jannis Drangmeister; Markus Kästner; Eduard Reithmeier (Sensors)
Endoscopic fringe projection is used to perform inspections of hard-to-reach areas. In order to transfer fringe patterns from a projector to the specimens’ surface, fiber optic imaging bundles (FOIB) can be employed. To ensure maximum accessibility, a highly flexible FOIB is needed. Therefore, the number of individual fibers has to be minimized, which affects the quality of the fringe pattern. This paper presents methods and results for projecting a high frequency pattern despite a small number of fibers by adapting the FOIBs’ structure. First, the spatial structure of the FOIB is identified with regard to the projector pixels. By determining their center, it is possible to address individual fibers. It will be shown that the peak values of spots produced by individual fibers behave nonlinearly according to the modulated intensity. Furthermore, the intensity distribution within the spots changes. By recording the intensity curves, the presented algorithm is able to adapt the fringe pattern in orientation and intensity. This leads, especially for high frequency patterns, to an improved amplitude and signal-to-noise ratio.